Students' satisfaction with a dental summer programme and importance of influencing factors for choosing dentistry as their career. (3rd October 2013) - Suen, R. P. C.; Lai, S. M. L.; Bridges, S.; Chu, C. H.
Abstract Aim To study the students' satisfaction with the week‐long summer programme and the importance of common influencing factors (IFs) for choosing dentistry as their career. Methods Anonymous questionnaire was given to all 214 participants in July of 2011 and 2012. Demographic information including gender, age and education level was collected. The students were asked about their satisfaction with the programme with separate ratings for learning experiences, including hands‐on workshops (HOW); clinic observations (CO); problem‐based learning tutorials (PBL); and lectures (L). They also rated the relative importance of the ten common IFs. The Friedman test was used to study the order of their preferences of the programme's activities. The Chi‐square test was used to study the influence of their demographic factors on the importance of the IFs. Results A total of 208 students returned their questionnaires. The majority were below the age of 18 (81%), and 44% were studying in an international school. Most of the students (96%) were satisfied with the programme overall. They liked the HOWs and COs more than the PBL tutorials and Ls. 'Altruism' and 'medical/health care career' were the two most important IFs overall. 'Altruism' and 'past experience with dentist' were considered more important by those aged 18 or above. 'Past experience with dentist' and 'working with hands' were considered more important by the international school students. Conclusions Most participants were satisfied with the summer programme. They preferred practical, skill‐based activities to knowledge‐based activities. The importance of some IFs was associated with age and education system.